Africa : unity, sovereignty, and sorrow - Englebert, Pierre, 1962- (Boulder, Colo. : Lynne Rienner Publishers, 2009)
Explores the endurance of Africa's weak states which, despite their failure to protect and promote the interests of their citizens, translate international sovereignty into domestic legal command.
The resilience of the African state -- The puzzle of territorial integrity -- The enduring authority of weak states -- The domestic currency of international sovereignty -- The calculus of compliance -- Separatist illustions and sovereignty variations -- The politics of unity and estrangement -- Sovereignty's shackles -- Rational policy fantasies.
Includes bibliographical references and index.
Keywords: Legitimacy of governments -- Africa, Sub-Saharan.; Sovereignty -- Social aspects -- Africa, Sub-Saharan.; Africa, Sub-Saharan -- Politics and government -- 21st century